A NON-EXPERIMENTAL STUDY TO ASSESS THE LEVEL OF PERCEPTION, PERFORMANCE AND SATISFACTION TOWARDS ONLINE LEARNING DURING COVID-19 PANDEMIC AMONG UNDERGRADUATE PHYSIOTHERAPY STUDENTS IN EMAAR GREENS, JAIPUR - Chauhan, Tarun; Gupta, Deeksha; Kumari, Sammi (International Journal For Research In Health Sciences And Nursing, 2022)
E-learning plays a vital role in this current scenario among students across the globe. The aim of this study was to evaluate the level of perception, performance and satisfaction regarding online learning during Covid-19 pandemic among undergraduate physiotherapy students. A quantitative approach with a non-experimental descriptive research design with 60 undergraduate physiotherapy students were recruited as study participants using a non-probability sampling technique for this study. According to the research study conducted by Abbasi Maria S. in 2020 stated that E-learning satisfaction levels were better among developed countries (7.34) compared to developing countries (5.82). The majority of participants agreed that E-learning was satisfactory in acquiring knowledge, however not effective in acquiring clinical and technical skills. As the COVID-19 lockdown eases, there is a need for improvement in the methods employed in E-learning and more blended learning among healthcare students is recommended. Data were collected using a self-structured questionnaire both for demographic information and to assess their level of perception, performance and satisfaction with online learning. The result of this study showed that the majority (50%) of the 30 physiotherapy students were between the ages of 19 and 20. By gender, 39 (65%) were women. In terms of religion, 38 (63.3%) were Hindu. 42 (60%) of them in the Bachelor of Physiotherapy program were in their junior year. Regarding prior information, 36 (60%) received updates via social media. It has also found that the current Level of Awareness, Performance and Satisfaction of Physiotherapy Students with Online Learning 7%) were found to have moderate awareness. Low awareness, 8 people (13.3%) had high awareness. Current online learning outcomes were 44 (73.3%) fair, 13 (21.7%) good and 3 (5%)) bad. Current satisfaction results showed that 44 people (73.3%) were moderately satisfied with online learning, 12 people (20%) were very satisfied, and 4 people (6.7%) were not satisfied. For this study, the mean score and standard deviation of current level of perception, performance and satisfaction with online learning among undergraduate physiotherapy students were 31.28±6.27, 33.20±5.54,33.35±6.29 with a minimum score of 14.0, 15.0 and 10.0, maximum score 43.0, 50.0 and 50.0. Furthermore, it has also showed that the association between current level of perception, performance and satisfaction with online learning among undergraduate physiotherapy students with their selected demographic variables None of the demographic variables showed a statistically significant relationship with current level of perception, performance and satisfaction with online learning among undergraduate physiotherapy students. The aim of this study was to evaluate the level of perception, performance and satisfaction regarding online learning among undergraduate physiotherapy students during covid-19 pandemic in Emaar Greens, Jaipur. Therefore, it was concluded that the current level of perception and satisfaction was average with fair performance towards online learning among undergraduate physiotherapy students.